1989
DOI: 10.2307/3566082
|View full text |Cite
|
Sign up to set email alerts
|

Niche Differentiation of Ant Species within Territories of the Wood Ant Formica polyctena

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. . Wiley-Blackwell and Nordic Society Oikos are collaborating with JSTOR to digitize, preserve and extend access to Oikos. Savolainen, R. and Vepsalainen, K. 1989. Niche differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 29 publications
6
74
0
Order By: Relevance
“…The two Formica species were observed on the same plants (or tubes of sucrose solution) as those exploited by M. sabuleti. Temporal segregation ensures a partial decrease of competition between M. sabuleti and the two Formica species: the foragers of M. sabuleti avoid the warmer hours of the day, whereas the foragers of Formica are particularly active during these hours (see also Savolainen and Vepsäläinen, 1989;Deffernez et al, 1990). This temporal segregation was mainly observed in the experiments with sugar baits, whereas the frequency of M. sabuleti increased from morning to evening on the extrafloral nectaries of V. sativa.…”
Section: Distribution Of Ants On Food In the Fieldmentioning
confidence: 81%
See 1 more Smart Citation
“…The two Formica species were observed on the same plants (or tubes of sucrose solution) as those exploited by M. sabuleti. Temporal segregation ensures a partial decrease of competition between M. sabuleti and the two Formica species: the foragers of M. sabuleti avoid the warmer hours of the day, whereas the foragers of Formica are particularly active during these hours (see also Savolainen and Vepsäläinen, 1989;Deffernez et al, 1990). This temporal segregation was mainly observed in the experiments with sugar baits, whereas the frequency of M. sabuleti increased from morning to evening on the extrafloral nectaries of V. sativa.…”
Section: Distribution Of Ants On Food In the Fieldmentioning
confidence: 81%
“…and Vepsäläinen, 1989). Traniello (1983) suggested that "in the case of generalist, opportunistic ant species, partitioning may be behavioural, based at least in part on differences in social methods of foraging".…”
Section: Distribution Of Ants On Food In the Fieldmentioning
confidence: 99%
“…Because of the small colony size (Savolainen 1990) and opportunistic foraging, colonies of F. fusca may survive within small patches of suitable habitat between the trunk trails of F. polyctena, where the average density of foraging F. polyctena individuals is low (Savolainen and Veps/il/iinen 1989). However, foragers of F. fusca are likely to encounter F. polyctena individuals.…”
Section: Discussionmentioning
confidence: 99%
“…A noncooperative two-nest system of F. polyctena studied closely in recent years has about one million foragers and territories extending at least 100 m from the mounds (Pisarski and Veps~ilfiinen 1989). Around the mound the foragers patrol at high densities up to 40 m off the mound, both in the open, exposed rocky outcrop and in the forest, and occupy all vertical layers above the litter (Savolainen and Veps/il/iinen 1989). Within the territories of F. polyctena the cryptic nests of F. (Serviformica) fusca may be found even 20 m from the wood-ant mounds.…”
Section: Introductionmentioning
confidence: 95%
“…F. polyctena and F. rufa), well-known for their restrictive impact on lower-ranked species (Mabelis 1984, Pisarski & Vepsalainen 1989, Savolainen & Vepsalainen 1989, Savolainen et al 1989, Punttila et al 1991. The community-structuring role of these species can be revealed, when ant communities with and without them are analyzed -as e.g.…”
Section: R E S U L T Smentioning
confidence: 99%